The Decline of Colombian Private Higher Education - Uribe, Lina (International Higher Education, 2010)
Colombian higher education experiences a recent private-sector decline despite its traditional dominance over public institutions. Though historically, Colombia has largely grown its higher education system as a result of the private initiative, the recent private sector's downfall is due to the astonishing public education growth and possibly the increased tuition for private institutions, reducing affordability, and shrinking the tuition gap between public and private institutions.